Vulnerability analysis of steel roofing cladding: Influence of wind directionality. (1st February 2018) - Ji, Xiaowen; Huang, Guoqing; Zhang, Xinxin; Kopp, Gregory A.
Highlights: An integrated damage estimation method for steel roofing claddings in high winds is proposed. Both the wind loading correlation and wind directionality effects are considered in the method. Results show wind loading correlation may noticeably increase the damage variation. Results show wind directionality may lead to a larger damage risk for claddings. Abstract: Steel roofing is widely used for non-residential facilities. However, it is vulnerable to high winds. This paper addresses a damage estimation framework that incorporates wind loading correlation and wind directionality effects for steel roofing. In this framework, external pressures were measured from wind tunnel testing. At positions where pressure measurements are not available, a proper orthogonal decomposition (POD) method is introduced to interpolate external wind pressures. Internal pressures due to openings in the building envelope are taken into account by simulation. Then, the internal forces on fasteners distributed on the steel roof are evaluated by the influence-surface-based method, with corresponding peak values estimated by a Gumbel conversion approach. Furthermore, the failure probability of a single cladding element and the damage ratio for the whole roof are determined based on Monte Carlo simulation (MCS), where the correlation among internal forces of fasteners is incorporated by a Nataf transformation. Finally, wind directionality effects are integrated in order to provide a comprehensive damage assessment for the roofing. Although the proposed framework works for existing buildings, it may potentially benefit the performance-based design for new low-rise buildings.